2013
DOI: 10.1128/jb.00821-13
|View full text |Cite
|
Sign up to set email alerts
|

MecA Protein Acts as a Negative Regulator of Genetic Competence in Streptococcus mutans

Abstract: c Streptococcus mutans develops competence for genetic transformation through a complex network that receives inputs from at least two signaling peptides, competence-stimulating peptide (CSP) and sigX-inducing peptide (XIP). The key step of competence induction is the transcriptional activation of comX, which encodes an alternative sigma factor, SigX ( X ), controlling the expression of late competence genes essential for DNA uptake and recombination. In this study, we provide evidence that MecA acts as a nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 46 publications
3
68
0
Order By: Relevance
“…Phenotypic characterization of an S. thermophilus clpC mutant revealed that ClpC plays a role in the development of genetic competence in this organism (310). The alternative sigma factor ComX, which drives the expression of competence genes, was shown in S. thermophilus and S. mutans to be under posttranslational regulation by ClpCP through active degradation (310)(311)(312)(313). This task is performed by ClpEP in S. pneumoniae (314).…”
Section: Treating Damaged Macromoleculesmentioning
confidence: 99%
“…Phenotypic characterization of an S. thermophilus clpC mutant revealed that ClpC plays a role in the development of genetic competence in this organism (310). The alternative sigma factor ComX, which drives the expression of competence genes, was shown in S. thermophilus and S. mutans to be under posttranslational regulation by ClpCP through active degradation (310)(311)(312)(313). This task is performed by ClpEP in S. pneumoniae (314).…”
Section: Treating Damaged Macromoleculesmentioning
confidence: 99%
“…Besides the transcriptional control of comX by the ComRS signaling system, the activity of X was also shown to be the target of a posttranslational negative control in one representative species of the pyogenic (25,29), salivarius (30,31), and mutans (32) groups. In these species, extensive in silico analyses did not allow the identification of a ComW homolog, suggesting that the regulatory system could be different from that in S. pneumoniae.…”
mentioning
confidence: 99%
“…In these species, extensive in silico analyses did not allow the identification of a ComW homolog, suggesting that the regulatory system could be different from that in S. pneumoniae. We and others have shown that the adaptor protein MecA and the ClpC ATPase subunit act as negative regulators of competence development in both S. thermophilus (30,31) and S. mutans (32). These studies revealed that the expression of late com genes and the abundance of X were increased in MecA-and ClpC-depleted strains compared to the isogenic wild-type (WT) strains (30)(31)(32) In addition, bacterial two-hybrid (B2H) assays suggested that MecA could interact in vivo with both X and ClpC (31,32).…”
mentioning
confidence: 99%
“…The low percentage of activation observed in the L. monocytogenes background (even with the overexpression of both regulators) suggests the existence of a strong negative regulation in the majority of the population. One candidate is the negative competence regulator MecA, which negatively regulates ComK in B. subtilis (42) and H in Streptococcus mutans and Streptococcus thermophilus (43,44). Further studies on H negative regulation are necessary to gain insight into the specific conditions that trigger the expression of competence genes.…”
Section: Discussionmentioning
confidence: 99%